EDUKASI PIJAT OKETANI DALAM PENANGANAN BENDUNGAN ASI DI KABUPATEN BULUKUMBA: EDUKASI PIJAT OKETANI DALAM PENANGANAN BENDUNGAN ASI DI KABUPATEN BULUKUMBA - Husnul Khatimah; Sumarni Sumarni; Haerani Haerani; A.Tenri Fajriani (JCS, 2023)
Failure in the breastfeeding process often occurs due to several problems that arise in post partum mothers, including lack of flow of milk which occurs in cases of breast milk dams. Damage in breast milk (Breast Engagement) is caused by increased venous flow of lymph in the breast which causes a feeling of fever, redness, swelling and hardening. One treatment that can be done to correct the problem and speed up breast milk production is an oketani massage. Oketani massage is a complementary therapy with breast care methods to increase breast milk production. Oketani massage can stimulate the strength of the pectoralis muscle to increase breast milk production and help the consistency of the breasts become elastic and reduce the incidence of breast milk dams in breastfeeding mothers. The aim of this service is to examine the effectiveness of oketani massage in preventing and treating postpartum mothers who experience breast milk dams and in increasing breast milk production. The population for this service is 6 postpartum mothers in Bonto Bulaeng Hamlet, Padang Village, Kab. Bulukumba. Outreach activities regarding Oketani Massage Education in Handling Post Partum Breast Milk Dams in Bonto Bulaeng Hamlet, Padang Village, Gantarang District, Kab. Bulukumba has been implemented well based on planning based on the enthusiasm of the mothers involved in participating in this activity. This activity was carried out to increase mothers' knowledge about Oketani Massage Education in Handling Breast Milk Dams.